GEOPHYSICAL FORENSIC FOR ARCHAEOLOGICAL EXPLORATION IN MUAROJAMBI, INDONESIA - Bambang Sugiarto; Dicky Muslim; Iyan Haryanto; Zufialdi Zakaria; Emy Sukiyah; Vijaya Isnaniawardhani; Achmad Djumarma Wirakusumah; Heryadi Rachmat (Program Studi Fisika Universitas Negeri Jakarta, 2020)
In July 2011, archaeological exploration tried to apply the physics method for the first time in Muarojambi, Indonesia. We combined physics with geosciences and called it geophysical forensic. Our method is known as Ground Penetrating Radar (GPR). GPR used high-frequency electromagnetic (EM) waves between 10-3000 MHz to imaging subsurface based on dielectric permittivity’s physical parameters. Changes in the electrical properties, rock magnetism, and water content of the material under the surface will provide a response recorded on the radargram as a function of distance to time (two-way travel time). Data processing performs to reduce the noise recorded when collecting data. We have successfully obtained four GPR lines; three lines gathered near Gumpung Temple and one line at Telago Rajo Pool. The GPR method succeeded in giving a subsurface image and possibility of the archaeological objects near the Gumpung Temple and Telago Rajo Pool.